Ultra-som anorretal bi-dimensional dinâmico no diagnóstico de anismus em mulheres adultas : estudo comparativo à manometria anal e ultra-som anorretal tri-dimensional dinâmico - Barreto, Rosilma Gorete Lima (2007)
Anismus is one of the most frequent disease in carrying patients of obstructed defecation and it is being present in about 50.0% of the constipated patients. The aim of this study is to demonstrate the use of the bi-dimensional anorectal ultrasound (2-D USD) for the diagnosis of anismus and comparing the results with the anus manometry and the three-dimensional anorectal ultrasound (3-D USD). Sixty adult women with obstructed defecation symptoms were evaluated in this prospective and comparative study, coming from Colorectal Unit of the Hospital Universitário Walter Cantídio of the Universidade Federal do Ceará, between September 2006 to March 2007. All the patients were initially submitted to anus manometry (BAD) and then divided in two groups with 30 patients each. Group I was formed by patients without anismus at the mean age of 48,63 (24 the 69) years, while group II with carrying patients with anismus at the mean age of 51,20 (27 the 78) years. After that, patients of both groups were submitted to the 3-D and 2-D USD by an examiner who was unaware of the results of the manometries. The average size of the gotten angle with the 3-D USD at rest position of group I was 87.28º ± 0.80º (76,5º-96,2º) and of 87.87º ± 0.99º (78,5º-109,4º) in group II. (p=0,3220). The average size of the angle during the evacuatory effort of group I was of 93.25º ± 1.49º (74,9º-106,9º) and of 85.27º ± 1.35º (72,0º- 101,8º) in group II, (p=0.007). The average size of the gotten angle with the USD 2-D at rest positions of group I was 62.61º ± 1.15º (50,9º-75,0º) and of 65.51º ± 0.89º (50,8º-73,0º) in group II (p=0,0257). The average size of the angle during the evacuating effort of group I was of 59.75º ± 1.42º (44,0º-73,0º) and of 69.40º ± 1.06º (52,6º-79,5º) in group II, (p< 0,001). Comparing the differences of the angles size at rest position and during evacuatory effort of the patients of group I with group II, using 2-D and 3-D USD, there was statistically significant difference (p< 0,0001). Comparing the results between the 2-D USD with the manometry, there was agreement in 86,67% and 83,33% of the patients of group I and group II respectivelly. Comparing the results between the 2-D and 3-D USD, there was agreement of 93,33% in the evaluation of the patients of group I and of 90,0% of the patients of group II. The agreement among the three methods was 86,67% as positive predictive value and 83.33% as negative predictive value. It is concluded that the use the 2-D USD was considered efficient in the diagnosis of anismus by the high indication of agreement among the three used methods.